Abnormal lipoprotein metabolism and reversible female infertility in HDL receptor (SR-BI)–deficient mice - Miettinen, Helena E. (American Society for Clinical Investigation, 2001)
Mammalian female fertility depends on complex interactions between the ovary and the extraovarian environment (e.g., the hypothalamic-hypophyseal ovarian axis). The role of plasma lipoproteins in fertility was examined using HDL-receptor SR-BI knockout (KO) mice. SR-BI KO females have abnormal HDLs, ovulate dysfunctional oocytes, and are infertile. Fertility was restored when the structure and/or quantity of abnormal HDL was altered by inactivating the apoAI gene or administering the cholesterol-lowering drug probucol. This suggests that abnormal lipoprotein metabolism can cause murine infertility — implying a functional hepatic-ovarian axis — and may contribute to some forms of human female infertility.